Production and purification of Bacillus anthracis protective antigen - Simson Tarigan; Rahmat S Adji; Lily Natalia (Jurnal Ilmu Ternak dan Veteriner, 2005)
Protective antigen (PA) plays crucial roles in the pathogenicity and virulence of Bacillus anthracis. Animals or human immunised with the protein acquire a complete protection against the disease. In addition to vaccine, PA can also be developed into a sensitive diagnostic test for anthrax. The purpose of this study was to produce PA using a culture medium easily obtained, and to develop a simple and effective technique for purification of the protein. To produce PA, B. anthracis Sterne 34F2 strain was first grown on blood agar, then bacterial colonies were suspended and incubated for 2 hours in RPMI-1640 supplemented with NaHCO3 and Tris. Protein components in the culture supernatant were separated consecutively with Phenyl sepharose, Qsepharose and Superdex-200 columns. This order was used in order to simplify and speed up the purification process. The PA contained in the fractions was detected by a dot blot or an ELISA using commercial PA specific antibody. The PA was absorbed strongly by the phenyl sepharose whereas other proteins were absorbed weakly or not absorbed at all. When these PA-containing fractions were loaded into Q-sepharose column, PA was absorbed considerably weaker than contaminated proteins. Although the level of purity obtained from the Q-sepharose column was satisfactory, further separation on Superdex produced an even higher purity. However, on SDS-PAGE analysis, the purified PA was seen as a two-band protein (54.7 and 29.2 kDa) because of nicked proteolysis. On an immunoblot assay, only the 54.7 band was recognised by the PA-specific antibody. Despite the nick proteolysis, the PA purified in this study was considered to retain its biological activities.     Key Words: Bacillus anthracis, Protective Antigen, Protein Purification